2022
DOI: 10.7883/yoken.jjid.2021.164
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Diagnostic Algorithms for Serodiagnosis of Syphilis

Abstract: We analyzed the performance parameters of the traditional and the reverse algorithms to find out which one is more convenient for serodiagnosis of syphilis. In total, 4789 serum samples were obtained in a cross-sectional study. Venereal Disease Research Laboratory (VDRL), Treponema pallidum Haemagglutination Assay (TPHA) and Chemiluminescent Microparticle Immunoassay (CMIA) tests were performed for every serum sample. In case of discordance between results, the TPHA was applied as a second treponemal test. Ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
2
0
2
Order By: Relevance
“…In contrast, Evren et al. 43 found that the rate of missed diagnoses of the traditional algorithm was 42.5%. The reverse algorithm (99.85%) had a higher sensitivity than that of the traditional algorithm (57.49%).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…In contrast, Evren et al. 43 found that the rate of missed diagnoses of the traditional algorithm was 42.5%. The reverse algorithm (99.85%) had a higher sensitivity than that of the traditional algorithm (57.49%).…”
Section: Discussionmentioning
confidence: 89%
“…30,42 No difference was found when assessing the sensitivity, specificity, and accuracy of the traditional and reverse algorithms. In contrast, Evren et al 43 found that the rate of missed diagnoses of the traditional algorithm was 42.5%. The reverse algorithm (99.85%) had a higher sensitivity than that of the traditional algorithm (57.49%).…”
Section: Discussionmentioning
confidence: 89%
“…Yıllık yüz binde 3.35'lik insidansın, sifiliz vakalarının farklı tanılar ile tedavi edilmesi ve bildirimin kısıtlı olmasından etkilendiği için düşük seviyede kaldığını düşünmekteyiz. Ülkemizden yapılan ters tanı algoritması kullanılan yakın tarihli bir çalışmada yaklaşık %4'lük bir seropozitiflik oranı saptanmıştır (4) . Taranan örnek sayısının görece kısıtlı olması elde edilen oranın çalışmamızda elde edilen orandan yüksek çıkmasını açıklayabilir.…”
Section: Discussionunclassified
“…A descentralização de testes rápidos de sífilis em serviços de atenção primária à saúde e maternidades podem proporcionar o diagnóstico precoce. Evren, et al (2022).…”
Section: Indicamunclassified